Georgia O'Keeffe : She Saw the World in a Flower - Balkan, Gabrielle; Bloggs, Josy; Metropolitan Museum of Art (New York, N.Y.) (New York, NY : DK Publishing, 2021)
A picture book biography of the life of American painter Georgia O'Keeffe. Includes a time line of her works as well as related art appreciation activities.
Includes bibliographical references.
Keywords: O'Keeffe, Georgia, -- 1887-1986 -- Juvenile literature; O'Keeffe, Georgia, -- 1887-1986; Painters -- Biography -- United States; Painting, American -- Juvenile literature; Women -- Biography; Artists; Painting, American; Women; Creative nonfiction; Biographies; Picture books